Pengaruh Earning Per Share (Eps), Return On Asset (Roa), Dan Nilai Tukar Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdaftar Di Bei Tahun 2021-2023 - Ferdi Rahmawinata; Elfiswandi .; Rindy Citra Dewi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of Earnings Per Share (EPS), Return on Assets (ROA), and exchange rates on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This research is quantitative. The sample was determined using a purposive sampling method to select companies that meet the research criteria. Data analysis methods used included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Data processing in this study used SPSS 25 software. The results indicate that EPS, ROA, and exchange rates partially significantly influence stock prices. EPS, ROA, and exchange rates simultaneously significantly influence stock prices. Based on these results, it is recommended that future researchers extend the observation period and include other variables that could potentially influence company value to obtain more comprehensive results.